Design of a bioinspired tunable stiffness robotic foot. (April 2017) - Qaiser, Zeeshan; Kang, Liping; Johnson, Shane
Abstract: The human foot is capable of adapting to various diverse terrains, and this function is due, in part, to the foot's capacity of varying its stiffness in different anatomical regions. The purpose of this study is to develop an adaptable robotic foot by emulating the human foot's arch, horizontal tie (the plantar aponeurosis, midfoot ligaments, etc.), and its ability of varying its stiffness. The robotic foot is designed, analyzed, optimized and fabricated as a semi-circular arch with a horizontal tie consisting of a Tunable Stiffness Mechanism (TSM). The active number of coils in parallel/series configuration of concentric helical springs is changed to control the stiffness of the TSM. The arch stiffness and tunable stiffness range were optimized using the epsilon constraint method. Analytical and finite element modeling results closely match the experimental validation of both the tunable axial stiffness behavior of the TSM and tunable bending stiffness of the robotic foot assembly. The results also show that the TSM is capable of varying the potential energy storage at midstance depending on the load or displacement applied. In conclusion, a robotic foot was developed to adapt to various diverse terrains through varying stiffness and therefore potential energy stored at midstance; the potential energy is then available for an elastic rebound and propulsion in the terminal phase of gait. By implementing proper control algorithms, the proposed tunable stiffness robotic foot is capable of real-time adaptations to changing terrains, which may lead to the design and development of more adaptive industrial and bipedal walking robots. Abstract : Highlights: A robotic foot assembly is developed to bio-mimic human foot with tunable stiffness. A novel tunable stiffness mechanism is proposed with linear stiffness response. Analytical model developed to compute deformation of TSM with an arch structure. Multiobjective optimization is performed to design tunable stiffness robotic foot. Components and assembly experimentally validated and energy storage is studied.